Cognitive reserve as a moderator of the negative association between mood and cognition: evidence from a population-representative cohort. Issue 1 (19th May 2017) - Opdebeeck, C.; Matthews, F. E.; Wu, Y-T.; Woods, R. T.; Brayne, C.; Clare, L.; ,
Abstract : Background: Cognitive reserve (CR) has been associated with better cognitive function and lower risk of depression in older people, yet it remains unclear whether CR moderates the association between mood and cognition. This study aimed to investigate whether a comprehensive indicator of CR, including education, occupation and engagement in cognitive and social activities, acts as a moderator of this association. Methods: This was a cross-sectional study utilising baseline data from the Cognitive Function and Ageing Study II (CFAS II), a large population-based cohort of people aged 65+ in England. Complete data on the measures of CR, mood and cognition were available for 6565 dementia-free individuals. Linear regression models were used to investigate the potential modifying effect of CR on the association between cognition and mood with adjustment for age, sex and missing data. Results: Levels of CR did moderate the negative association between mood and cognition; the difference in cognition between those with and without a clinical level mood disorder was significantly smaller in the middle (−2.28; 95% confidence interval (CI) −3.65 to −0.90) and higher (−1.30; 95% CI −2.46 to −0.15) CR groups compared with the lower CR group (−4.01; 95% CI −5.53 to −2.49). The individual components of CR did not significantly moderate the negative association between mood and cognition. Conclusion: These results demonstrate that CR, indexed by a composite score based on multiple indicators, can moderate the negative association between lowered mood and cognition, emphasising the importance of continuing to build CR across the lifespan in order to maintain cognitive health.